Subcarpathia in the perspective of parliamentary elections in 2015 - Szczepański, Dominik (Political Preferences, 2016)
Subcarpathian voivodeship that was formed in 1999 in result of the administrative reform preserved voting traditions from all former voivodeships that comprise the current territorial unit of the country. It is noteworthy that the most important factors that significantly influenced electoral preferences of the Subcarpathia voivodeship were dominating electoral habits after 1989; electoral system elements, selected socio-economic indicators, as well as historical and religious determinants. The abovementioned factors are also supported by the positively verified partitions hypothesis, according to which it is assumed that in each partition area different patterns of political culture as well as various dominating political and ideological orientations were formed. This process was determined by policies of partitioning powers towards Polish citizens in the annexed areas, as well as the character and way of organising state by partitioning powers, the level of their economic and cultural development. It was by means of following tradition that the above patterns are passed from generation to generation, which firstly confirms its timelessness, and secondly finds its reflection in election results in Subcarpathia. Key words: elections behaviour, parliamentary elections, electoral, Poland, Subcarpathian Voivodeship